Novas tendências do sindicalismo brasileiro: a formação do Sindicato Estadual dos Profissionais da Educação (SEPE - Regional V) no período de 1979-1990 - Silva, Rita de Cassia da (2006)
The approach about the formation of the Union of Education Professionals of the State of Rio de Janeiro (SEPE), had as sampling the Regional V, situated in Campo Grande, West of the city of Rio de Janeiro, based on the premise that the formation of this regional unit is part of the historical memory of the New Unionism, was developed through methodological instrument of blibiographical research, statistic data, maps, and data analysis compiled in interviews with for-mer heads and militants of SEPE/Regional V, area where the research was fulfilled.